PERAN PROFITABILITAS DALAM MEMODERASI PENGARUH INTELLECTUAL CAPITAL, LEVERAGE, DAN SALES GROWTH TERHADAP FINANCIAL DISTRESS - Mulyatiningsih, Nunung; Atiningsih, Suci (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2021)
This study aims to provide empirical evidence regarding the role of profitability in moderating the effect of intellectual capital, leverage and sales growth on financial distress. The population of this research is infrastructure, utility and transportation sector companies listed on the BEI from 2014 to 2018 with a total sample of 155 companies. Sampling in this study using purposive sampling method and using the statistical test tool is PLS-SEM with the WarpPLS 5.0 program. The results showed that intellectual capital has a negative effect on financial distress. Leverage has no effect on financial distress. Sales growth has a positive effect on financial distress. Profitability can moderate the effect of intellectual capital on financial distress, but profitability was can not moderate the effect of leverage and sales growth on financial distress. Contribution to investors is taken into consideration before making a decision to invest in a company, namely by paying attention to the financial statements and financial ratios in order to find out the good and bad effects of financial distress in the company.